2005
DOI: 10.1007/s00125-005-1874-4
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and its analogue glargine do not affect viability and proliferation of human coronary artery endothelial and smooth muscle cells

Abstract: Aims/hypothesis: Present guidelines for the treatment of type 2 diabetes recommend HbA 1 c values of less than 7%. As beta cell function worsens during progress of the disease, insulin therapy is often necessary to achieve this ambitious goal. However, due to peripheral insulin resistance, many patients need rather high insulin dosages. In the light of the extremely high cardiovascular risk of diabetic patients, it is important to determine whether high concentrations of insulin or its frequently used analogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
7
24
1
1
Order By: Relevance
“…Although an increase in mortality rate was observed in male rats at every glargine dose and in female rats in the high-dose glargine group, these results are consistent with the prevailing view that regular insulin and insulin analogues, per se, do not induce malignant transformation. Furthermore, neither regular insulin nor glargine were shown to affect viability and proliferation of non-transformed human coronary endothelial and smooth muscle cells [30].…”
Section: Discussionmentioning
confidence: 93%
“…Although an increase in mortality rate was observed in male rats at every glargine dose and in female rats in the high-dose glargine group, these results are consistent with the prevailing view that regular insulin and insulin analogues, per se, do not induce malignant transformation. Furthermore, neither regular insulin nor glargine were shown to affect viability and proliferation of non-transformed human coronary endothelial and smooth muscle cells [30].…”
Section: Discussionmentioning
confidence: 93%
“…Since increasing evidence, mainly from histological examinations, suggests endothelial cell apoptosis to play an important role in atherogenesis, plaque erosion, and acute coronary syndromes (7,8), we studied the susceptibility of endothelial and smooth muscle cells from human coronary arteries toward NEFA-induced apoptosis (lipoapoptosis). As we recently reported, the saturated NEFAs palmitate and stearate, at high physiological concentrations, provoke substantial apoptotic events in human coronary artery endothelial cells (HCAECs) and a mixed form of apoptosis and necrosis in human coronary artery smooth muscle cells (9). To further characterize these findings, we investigated in this study the role of selected saturated versus unsaturated NEFAs in HCAEC lipoapoptosis and the underlying molecular mechanisms.…”
mentioning
confidence: 86%
“…Most of these studies were done in tumour cell lines or in cell systems overexpressing the human InsR and thus do not represent the normal status of primary human cells. Recently, Staiger et al [23] reported that glargine and human insulin are not different in their proliferative effects on human coronary artery endothelial and smooth muscle cells.…”
Section: Introductionmentioning
confidence: 99%